Foreign Direct Investment: A Potential Export Platform for Pakistan - Hussain, Iftikhar; H. Memon, Manzoor (The Lighthouse Journal of Social Sciences, 2022)
Over the last two decades, developing countries, in particular have taken several policy measures to encourage inflows of foreign investment for the achievement of sustainable economic growth. Foreign investment not only brings and transfers the knowledge-based technology and managerial skills but also injects the most needed capital in the host economy. Further, the global linkage via foreign association enables the local product compatible with international standards. Thus, the country’s product demand increases in the international market. The research endeavors the motive of source countries to Foreign Direct Investment in Pakistan. Besides, examines the relationship between exports and FDI for the source country ‘United States of America (USA)’. From data analysis, it is revealed that FDI from the source country USA has a strong association with exports to them.